Research Laboratories: embodied research methodology in perfoming arts - Scialom, Melina (Revista Brasileira de Estudos da Presença, 2021)
The article discusses the concept of laboratory in performing arts by means of intersections between academic research and laboratory theatre. By using the term laboratory to describe bodily and scenic investigations that are conducted in the studio, a combination of artistic and academic activities are discussed in order to foster a methodology for embodied research in performing arts. To that end, we present examples of laboratory practice in researches based on theory and on Practice as Research. Finally, we indicate laboratory practice as a method that produces tacit-somatic knowledge and present a methodological proposal for laboratory practice in academic research.